The Role of the Family Environment in Arabic Language Acquisition among Native Speakers - Putri Maulani Rahmadita; Sofyan Sauri; Rinaldi Supriadi; Khidir Sumawikarta (Universitas Cokroaminoto Palopo, 2025)
Families who are actively involved the process of a child’s first language acquisition have an important role for their child. Therefore, the purpose of this research is to investigate the rule of the family environment in the the acquisition of Arabic as a first language among native-speaking family. This research employed a case study approach, and collecting data through intervie with the parents and by listen and take notes from the recorded conversation between the parents and child. The results of this study show that the family environment, especially active parents, has a significant role in their child’s acquisition of Arabic as their first language. This can be seen from the daily interactions between the family and the child and the vocabulary the child imitates from his family environment.